PENGARUH KOMISARIS INDEPENDEN, PERTUMBUHAN PENJUALAN, PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Achmad Wahyu Prasetyo; Nora Hilmia Primasari (Jurnal Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of Independent Commissioners, Sales Growth, Profitability, Leverage and Company Size on Tax Avoidance. The population in this study are mining companies on the Indonesia Stock Exchange for the 2016-2018 period. The method of determining the sample using purposive sampling technique with criteria. The analytical tool used is multiple linear regression and using SPSS version 20.0 program. The results of this study indicate that independent commissioners and profitability have a positive effect on tax avoidance, while sales growth, leverage and firm size have no effect on tax avoidance.